In vitro controlled release of extracellular vesicles for cardiac repair from poly(glycerol sebacate) acrylate-based polymers. (1st October 2020) - Hamada, Thomas; Dubois, Julie L.N.; Bellamy, Valérie; Pidial, Laetitia; Hagège, Albert; Pereira, Maria N.; Menasché, Philippe
Abstract: Cell therapy to restore cardiac function in chronic heart failure has been extensively studied. However, its therapeutic value is limited due to poor cell engraftment and survival and the therapeutic outcomes have been attributed to paracrine secretions such as extracellular vesicles (EV). The direct use of EV is an attractive therapeutic strategy and it has been shown that the kinetics of delivery of the EV to the targeted tissue may impact the outcomes. However, there are currently no technologies to deliver EV to the heart in a controlled and tunable manner. The objective of this study was to design a controlled release system, based on a photocurable adhesive polymer, to locally deliver EV to the cardiac tissue. We have first demonstrated that the adhesive polymer, PGSA-g-EG, did not impact the EV bioactivity in vitro and was biocompatible in vivo when tested in a rat model. Importantly, the polymer remained attached to the heart surface for at least 1 month. We have then evaluated and optimized the in vitro release kinetics of the EV from the PGSA-g-EG polymer. Freeze-dried EV formulations were developed to tune the release kinetics and maximize the loading in the polymeric material. Moreover, despite the instability of the EV in aqueous medium at 37°C, the PGSA-g-EG polymer was able to release bioactive EV for at least 14 days. Overall, these results suggest that the PGSA-g-EG is a suitable material to promote the controlled delivery of bioactive EV over an extended period of time. Statement of Significance: Extracellular vesicles (EV) are an investigational class of therapeutics that has shown promise to restore cardiac function following an ischemic event. Furthermore, its translation to the clinics is expected to pose less regulatory challenges than cell-based therapies. However, EV therapeutic outcomes are likely to be impacted by the route of administration and the kinetics of delivery to the target tissue. Therefore, there is a need for biomaterial-based technologies to deliver, in a controlled and tunable manner, EV to the heart. The present study describes the use of PGSA-g-EG polymer as an adhesive cardiac patch with potential to enable the controlled delivery of bioactive EV over an extended period of time to the cardiac tissue. Graphical abstract: Image, graphical abstract